Factors Associated with Loneliness among Adolescents in Thailand, Indonesia, Brunei Darussalam, and the Philippines - Lafi Munira; Bumi Herman (Asian Journal of Social Health and Behavior)
Introduction: Loneliness in adolescents in Southeast Asia has a prevalence range of 9.2%–14.4% and is associated with poorer mental health. This study aimed to identify factors associated with loneliness among adolescents in Indonesia, Thailand, the Philippines, and Brunei Darussalam. Methods: This cross-sectional study used secondary data from the most recent Global School-based Student Health Survey datasets for Indonesia (2015), the Philippines (2019), Brunei Darussalam (2019), and Thailand (2021), with a sample of 21,901 adolescents. Loneliness was the primary variable and analyzed with weighted data. Multinomial regression identified the significant factors associated with loneliness. Results: The prevalence of extreme loneliness was 4.7%, with the Philippines showing the highest rate. Factors significantly associated with “always lonely” include older age (odds ratio [OR]: 1.153, 95% confidence interval [CI]: 1.045–1.272), being female (OR: 3.419, 95% CI: 2.415–4.840), food insecurity (FI; OR: 1.531, 95% CI: 1.303–1.798), physically inactive (OR: 1.503, 95% CI: 1.358–1.664), good parental relationships (OR: 0.519, 95% CI: 0.373–0.723), and more close friends (OR: 0.623, 95% CI: 0.517–0.750). Whereas, insignificant effects were seen from good peer relationships (OR: 0.969, 95% CI: 0.823–1.140) and frequency of having physical attacks (OR: 1.059, 95% CI: 0.944–1.189). Conclusion: The findings emphasize the importance of national policies to address adolescent FI, promote physical activity, and incorporate mental health education in schools. Investment in accessible green spaces, parenting education, and comprehensive antibullying strategies in collaboration with parents, schools, and communities could help mitigate loneliness among adolescents.